Integrated management of yellow rust caused by Puccinia striiformis f. sp. tritici in wheat - Lavilla, M. (2023)
Introduction. Yellow rust caused by Puccinia striiformis f. sp. tritici, is currently the main disease of wheat (Triticum aestivum) in the north of the province of Buenos Aires, Argentina. It has caused yield losses close to 20 %. Objective. To evaluate the effect of different agronomic management systems on wheat yield and incidence of yellow rust. Materials and methods. The trial was carried out in the town of Pergamino, Buenos Aires, Argentina, during the years 2019, 2020, and 2021. The experimental design was in subdivided plots, the largest plot was with and without cover crop, the subplot was agronomic management, and the sub-subplot the application was foliar fungicide at different phenological stages of the wheat crop. Results. With the use of foliar fungicides in stages close to stem elongation and the use of a cultivar resistant to the disease produced a reduction in the area under the disease progress curve (AUCPE) by 62.50 %, which translated into significant grain yield increases of 29.52 %. Foliar fungicide application resulted in a 16.94 % increase in wheat yield. The implementation of a sustainable integrated management system generated yield increases of 29.52 %. Conclusions. The use of a resistant cultivar and the application of a foliar fungicide at early stages and with low levels of the disease, significantly reduced the AUCPE of yellow rust and increased the wheat yield in experimental plots.